ASUT LANGSUNG DAN PEMBEBANAN VARIABLE MOTOR INDUKSI - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2015)
There are still many books or papers in the Indonesian language explaining that big induction motors are not allowed with DOL (direct on line) starting. This paper will explain how DOL starting of big induction motors is possible. This paper also explain details about variable load of big induction motors.